Organizational and Economic Factors of Health System Optimization - Oleksandr Telizhenko; Yuliia Halynska; Nataliia Baistriuchenko; Volodymyr Potseluiev; Kateryna Demchuk (Health Economics and Management Review)
The article discusses approaches to optimizing the health care system in the context of reform. In the article identified institutional and organizational constraints to shape the health care system model with the necessary components: quality assurance, financial constraints, and optimization of budgetary resources. In the article developed the approaches to the formation of the health care system at the regional level. To this aim, the factors that influence the efficiency of the organization and functioning of the medical system are identified. Particular attention is paid to the organization of quality medical care in the united territorial communities of the Sumy region. The factorial analysis made it possible to form models of organization of medical institutions in the united territorial communities, taking into account financial and organizational constraints. In the process of research used the conditionally constant and variable factors in the model to adapt effectively to changes in the external environment. Modeling is based on a functional approach (model based on data flow construction). This approach allows you to identify functional problems of the system, to determine the basic requirements of stakeholders, to determine the structure of information flows in the model. In this case, the health care system is considered as a set of processes (related or independent) that achieve this goal. Then the overall management of the system can be represented as the management of a set of these processes in order to obtain the end result (with the specified characteristics). The peculiarity of this approach to modeling is to summarize a large array of input information, to establish direct and feedback between economic, demographic, geographical, social indicators of community development and medical indicators (results) that characterize the level of public health. The introduction of an integral indicator in the calculation model will solve both general institutional tasks, such as temporal dynamics within the created unified territorial community and creating a competitive position in comparison with other unified territorial communities of the region, and making local management decisions based on the influence of individual factors on the functioning of the health care system. The application of the model makes the practical importance in the control of deviation of the actual value of the integral indicator from the normative and planned result.